Polyol derived sulfonated solvothermal carbon for efficient dye removal from aqueous solutions - Zaman, Ali Can (ELSEVIER SCIENCE BV, 2018)
Solvothermal carbonization of ethylene glycol was employed for the synthesis of nanostructured sulfonated carbon in which sulfuric acid was used as the synthesis medium. The existence of sulfonic acid (SO3H), carboxylic acid (COOH), and many other functional groups was determined by FTIR and TG-FTIR (Thermogravimetric Analysis-Fourier Transform Infrared Spectroscopy). Synthesized bulk material consisted of 68.46 +/- 20.19 nm sized quasi-spherical carbon particles according to Scanning electron microscopy (SEM) observations. X-ray diffraction (XRD) analysis revealed that the material was a turbostratic type carbon. Formation mechanism of sulfonated solvothermal carbon (SSC) is believed to involve ethylene and ethylene glycol oligomers. Namely, carbon carbon bond forming reactions take place between aliphatic intermediate molecules under high temperature-high pressure conditions by constituting randomly oriented carbon aromatic frameworks connected by aliphatic short chains, meanwhile fractionalization (e.g., sulfonation) processes take place. Experimentally maximum adsorption capacity for methylene blue (MB) under basic conditions (pH 11) was determined to be 1472.61 mg g(-1) while initial MB/carbon weight ratio was 1500 mg g(-1) and over 96% removal was achieved within <240 min. It was demonstrated that SSC is an excellent adsorbent for the removal of dye pollutants from aqueous systems. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Solvothermal synthesis; Sulfonation; Carbon nanoparticle; Methylene blue; Water purification; Dye removal; ACTIVATED CARBON; METHYLENE-BLUE; FUNCTIONAL-GROUPS; AMORPHOUS-CARBON; GRAPHITE OXIDE; HYDROTHERMAL CARBONS; SURFACE-CHEMISTRY; MESOPOROUS CARBON; ADSORPTION; TEMPERATURE; Chemistry; Physics